Use of Nano composites in industries - Mohammed Ridha H Alhakeem (ITScience (Information Technology and Science), 2022)
High performance materials called Nano composites have unique features. Engineering plastics and elastomers are where Nano composites are most in demand, with an anticipated 25% annual growth rate. Their potential is so great that they are useful in many applications, from packaging to biomedical ones. The many forms of matrix Nano composites are covered in this review, with an emphasis on the need for these materials, their methods of manufacturing, and some recent findings regarding their structure, characteristics, and possible uses. The necessity for such materials in the future as well as other intriguing applications are projected. Applications of nano composites offer new technical and commercial potential for numerous sectors of the aerospace, automotive, electronics, and biotechnology industries because to their environmental friendliness.